Molecular Detection of Non-Tuberculous Mycobacterium and Cryptosporidium Co-Infections in Cattle - Sajjan, Santosh; Banagere Shekharappa, Pradeep; Srinivas Rao, Tumati; Chokkadabylu Benakabhat, Madhavaprasad; Suresh Bagalkote, Prashant (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Infectious diarrhea in young ruminants is a major problem, often involving co-infections with multiple pathogens like Cryptosporidium, non-tuberculous mycobacteria (NTM), and others. This study aims to investigate the prevalence of co-infections with NTM and Cryptosporidium in cattle using molecular techniques, acknowledging the potential for these pathogens to interact and modulate the course of diarrhea in cattle on an organized dairy farm in Bengaluru, Karnataka during 2019-20. A total of 17 crossbred cattle suffering with chronic diarrhea out of 82 cattle were screened for Mycobacterium and Cryptosporidium infections by conventional staining protocols and PCR. DNA extracted from fecal samples and rectal pinch was subjected to PCR targeting hsp65 gene (441 bp) specific to Mycobacterium. The multiplex PCR was also performed to identify species of Mycobacterium under MTB Complex (MTBC) using two pairs of primers (Rv1506c)that gave positive result to hsp65 gene. Further, Mycobacterium spp. was differentiated as MTBC or Non-Tuberculous Mycobacterium (NTM) by using a commercial qPCR kit. A two-step nested PCR protocol was followed to amplify 830 bp fragment of the 18S rRNA gene of Cryptosporidium. Out of 17 DNA samples, hsp65 gene (441 bp) specific to Mycobacterium genus was amplified in 6 samples, but none of them belonged to MTB complex. All the 6 DNA samples were identified as NTM by qPCR. Subsequently, all the 17 DNA samples were subjected to a two-step nested PCR protocol. Five samples out of them amplified 830 bp fragment of 18S rRNA gene of Cryptosporidium spp., which were also positive for NTM. This study signified the possibility of co-infection with Mycobacterium spp. and Cryptosporidium spp. in immuno-compromised chronic diarrheic crossbred cattle.